DISSOLUTION RATE OF PURE CaO AND INDUSTRIAL LIME IN CONVERTER SLAGS - Elizaveta Cheremisina (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2017)
In steelmaking process lime serves as flux. Rapid lime assimilation and slag formation of the desired composition have a significant effect on the refining reactions. It is important to know the rate limiting step of lime dissolution to control and improve the converter process. Kinetics of pure CaO and industrial lime dissolution in model slag has been studied in the range of temperatures 1300 –1600°C. Lime samples were prepared in cylinder form and immersed in the melt for predetermined time. Considering the total mass balance of CaO in the slag and linear dimensions of lime samples, mass transfer coefficients were derived. Diffusion coefficients were calculated under conditions of non-stationary diffusion. The derived activation energy of less than 200 kJ/mol indicates that diffusion is the limiting step in the process of lime-dissolution in slag.